2019
DOI: 10.1088/1755-1315/388/1/012004
|View full text |Cite
|
Sign up to set email alerts
|

New records of Scelio species (Hymenoptera: Scelionidae) from Iraq: egg parasitoids of acridid grasshoppers (Orthoptera: Acrididae)

Abstract: During insect surveys in June 2019 using yellow pan traps and sweep nets in agricultural areas of the Al Husayniya district of Karbala Governorate, three species of the economically important parasitoid genus Scelio were identified. Scelio howardi Crawford, S. striatus Priesner and S. variegatus Kozlov and Kononova all represent new records in Iraq. The current known distributions and host records of these three species are summarised, and their diagnostic features are illustrated. Previously unpublished host … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Some species of Platygastroidea were reported by Kononova & Kozlov (2008) from Turkey. Three species of Scelio Latreille, 1805 (Hymenoptera: Platygastroidea: Scelionidae) (Polaszek et al 2019) and Platygaster oebalus Walker, 1835 (Hymenoptera: Platygastridae) (Kareem et al 2020) have been reported from Iraq. A new genus and species of platygastrid flies, namely Psix abnormis Kozlov & Le, 1976, were described from Afghanistan (Kozlov & Le 1976).…”
Section: Discussionmentioning
confidence: 99%
“…Some species of Platygastroidea were reported by Kononova & Kozlov (2008) from Turkey. Three species of Scelio Latreille, 1805 (Hymenoptera: Platygastroidea: Scelionidae) (Polaszek et al 2019) and Platygaster oebalus Walker, 1835 (Hymenoptera: Platygastridae) (Kareem et al 2020) have been reported from Iraq. A new genus and species of platygastrid flies, namely Psix abnormis Kozlov & Le, 1976, were described from Afghanistan (Kozlov & Le 1976).…”
Section: Discussionmentioning
confidence: 99%